Origin and Dismeasure: the Thought of Sexual Difference in Luisa Muraro and Ida Dominijanni, and the Rise of Post-Fordist Psychopathology - Righi, Andrea (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
In Pensiero Vivente (2010), Roberto Esposito investigates the issue of origin as a crucial axis of inquiry for Italian philosophy. His acute reconstruction of Italian philosophical thought, however, dedicates little attention to feminism and to the philosophies of those who carry out the labor of procreation and reproduction. This essay reframes the problem of origin from the point of view of the maternal, exploring the thought of sexual difference in the work of two prominent militants of the Diotima philosophical Community: Luisa Muraro and Ida Dominijanni. The aim is twofold: study how the notion of the maternal symbolic can be understood as furthering Jacques Lacan’s construction of the feminine; show how the socio-psychological transformations produced by post-Fordism call for a rethinking of some of the basic assumptions of the maternal symbolic, particularly the notion of fixation.